Optimization on pretreatment of rubber seed oil using microwave-assisted technique - Trinh, H. (Japan Institute of Energy, 2017)
Recently, Rubber Seed Oil (RSO) has been considered as a promising potential oil source for biodiesel production. However, like other non-edible feedstocks, RSO contains a significant amount of high free fatty acids which affect the process of biodiesel production. In the present work, microwave-assisted esterification process was conducted as a pre-treatment step to reduce the high free fatty acid (FFA) content of RSO from 40.14 to less than 1. Response surface methodology (RSM) involving central composite design (CCD) was employed in the design of experiments (DOE) and the optimization of esterification reaction. The optimum conditions were found at 60 °C, with methanol to oil molar ratio of 19.94:1, H2SO4 catalyst of 7.93 wt and reaction time of 23 min. The result shows that methanol to oil molar ratio was the most influencing parameter towards the FFA reduction followed by temperature, whereas the catalyst loading and the reaction time both were observed to be insignificantly effective. © 2017, Japan Institute of Energy. All rights reserved.